EFFICACY OF GARLIC Allium sativum L. AQUEOUS EXTRACT IN CONTROLLING SAPROLEGNIA HATCHERY-LINKED INFECTION IN Clarias gariepinus (BURCHELL, 1822) - MSHELIA, B. U; USMAN, A.; HASSAN, M.Z.; SHETIMA, H. M.; MODU, B. M.; DIYAWARE, M. Y. (Nigerian Journal of Fisheries, 2024)
The efficacy of Garlic, Allium sativum L. aqueous extract in controlling Saprolegnia hatchery-linked infection in African Catfish Clarias gariepinus (Burchell,1822) were investigated. Fresh Allium sativum was procured from Maiduguri Monday Market, peeled, washed, and ground to obtain the garlic juice. The prevalence of saprolegnia on eggs, fry, and fingerlings was determined by submerging fertilized eggs into different concentrations of the garlic extract for 5 minutes, smear sample from each treatment were collected at different developmental stages of the fish, and samples were cultured on Sabourd Dextrose Agar (SDA). The experiment was carried out using a completely randomized experimental design with six (6) treatments and five (5) replicates. The data obtained were subjected to one-way analysis of variance, and the differences between the means were separated using Duncan Multiple Range test. The results obtained at egg stage showed total elimination of saprolegnia in T5 (2.0 mL/L) and T6 (2.5mL/L), with 40.8% as the highest, which was recorded in T1. Similarly, total elimination of saprolegnia was observed at fry stage in T4, T5, and T6, while highest prevalence of 48.6% was recorded in T1(control). At fingerling stage, total elimination of saprolegnia was observed in T3, T4, T5, and T6 and the highest prevalence of 10.2% was recorded in T1. Generally, there was a decrease in the occurrence of saprolegnia with increase in concentration of garlic extract and developmental stage of the fish.